Factors Predicting of Health Promoting Behaviors Among Undergraduate Students in Rangsit University - Panpoklang, Suparat; Faimuenwai, Romthanika; Kimsungnoen, Nipa (Journal of health and health management, 2025)
The purpose of this research were to investigate health promotion behaviors and factors predicting health promotion behaviors among undergraduate students in Rangsit University. The sample consisted of 438 students’ year 1-4 for the 2022 academic year. The Instruments utilized by the data collection consisted of 1) general information questionnaire 2) health promoting behaviors and 3) questionnaires on perceived benefit, perceived barrier, perceived self- efficacy, interpersonal influence, situational influences. General data were analyzed by using descriptive statistics. Pearson’s product moment correlation coefficient and multiple regressions were used to analyze the relations and the predictive power. The results of this study as follows: 1) The total mean score for health promoting behaviors was 2.37 (SD = .33), and had scores at a moderated level, while sexual risk behavior, smoking and alcohol consumption behaviors were low level 2) perceived benefits of health promoting behavior, perceived barriers of health promoting behaviors, perceived self-efficacy in health promoting behaviors, and interpersonal influence were significantly positive correlated at low to moderate level with health promoting behaviors (p<.05; r =.157, .231, 148, .401) but gender, faculty enrolled were significantly negative correlated at low level with health promoting behaviors (p<.05; r = -.193, -.130) 3) significantly predictors health promoting behaviors of Undergraduate Students in Rangsit University were gender, faculty enrolled, perceived benefits of health promoting behavior, perceived barriers of health promoting behavior, and perceived self-efficacy in health promoting behaviors (p<.05). The predictive power was 24.8% of the variance (Adjusted R2 = 0.248, p<.05). The results of this study suggested that it is vital and the administrators of Rangsit University should concern and integrate teaching or health promotion activities for improving health promoting behaviors among undergraduate students and provide a health promotion policy for undergraduate students to healthy.